Β-Mannosidosis in German Shepherd Dogs. Issue 5 (September 2019) - Jolly, Robert D.; Dittmer, Keren E.; Garrick, Dorian J.; Chernyavtseva, Anastasia; Hemsley, Kim M.; King, Barbara; Fietz, Michael; Shackleton, Nicola M.; Fairley, Robert; Wylie, Kirsten
A neurological disease was investigated in 3 German Shepherd pups from the same litter that failed to grow normally, appeared stiff, were reluctant to move, and were deaf. They developed intermittent seizures and ataxia and had proprioceptive defects. Histopathology showed severe vacuolation of neurons, astrocytes in nervous tissue, renal tubular epithelial cells, and macrophages in nervous tissue, spleen, and liver. Vacuoles appeared empty with no storage material stained by periodic acid–Schiff (PAS) or Sudan black stains, leading to a diagnosis of a lysosomal storage disease and in particular an oligosaccharidosis. Biochemical and genomic studies showed that this was β-mannosidosis, not previously diagnosed in dogs. A c.560T>A transition in exon 4 of the MANBA gene was found, which segregated in these and other family members in a manner consistent with it being the causative mutation of an autosomal recessive disease. This mutation led to substitution of isoleucine to asparagine at position 187 of the 885 amino acid enzyme, a change expected to have functional significance.